Estrategias de marketing digital para la comercialización en la Avícola Aviburz del cantón Bolívar - Zambrano Carreño, Andrés Antonio (2023)
The objective of this research was to establish digital marketing strategies that contribute to the commercialization of the Aviburz poultry farm in Bolívar canton. The research methodology used the inductive, deductive, and analytical-synthetic method to develop a series of analysis of the information collected and results obtained. Regarding the techniques, the use of the interview as a means to know the situation of the digital marketing strategies used in the Aviburz poultry farm is highlighted; also, the second technique used was the OGSM model as a planning model for the strategies developed. Regarding the tools used in the research, it is worth mentioning the use of a bibliographic reference manager software to organize the information through a database. In addition, Publish or Perish software was used to search for information in scientific databases and Atlas T.I. was used to carry out the qualitative analysis of bibliographic resources. The results found are based on a bibliographic review that showed which digital marketing strategies exist and provided a theoretical basis for the results obtained in the study. In the next phase, through the interview, factors to improve in the digital marketing strategies of the company were found and finally strategies were structured through a digital marketing brief, the use of the OGSM model to propose strategic actions and advertising content were designed in order to contribute to the commercialization of Aviburz poultry in Bolivar canton.